Automatic room temperature control - Jaafar, Lizawati (2013)
This project proposes an automatic room temperature controller, which uses the difference between the outside and inside room temperature. The difference is assumed to affect the compressor speed in order to achieve the desired set point. The frequency of the speed compressor is also taken into account. The project involves finding the mathematical model of an air conditioning system, designing a controller and performing a simulation to analyse the performance of the designed controller using Matlab/Simulink. The controller is based on adaptive fuzzy to control the temperature room. The result shows that the controller is able to follow the input reference and the output response of adaptive fuzzy control has better tracking performance. The developed system is hoped to address the issue of high cost electricity.